Pengaruh Model Pembelajaran CIRC berbantuan Media Thinker’s Track terhadap Kemampuan Membaca Pemahaman - meilia, Irma; Malihatul Hawa, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) model assisted by Thinker's Track media on reading comprehension skills. The research method used is a quantitative method with a Non-Equivalent Control Group Design. The population in this study was all students of SDN Candigaron. The research sample was class III of SDN Candigaron 03 as the experimental class and class III of SDN Candigaron 02 as the control class. The data collection techniques used were tests through pre-tests and post-tests as well as non-test techniques including observation questionnaires and documentation. Data analysis was performed using normality tests, homogeneity tests, and independent sample t-tests. The results showed that there was a difference in the use of the Cooperative Integrated Reading and Composition (CIRC) model assisted by Thinker 's Track media on reading comprehension skills. This is indicated by a significance value of 0.000 < 0.05 in the Independent Sample T Test, which shows that there is a difference in the quality of learning between the experimental and control classes. The mean score of the experimental class was 85.75, which was much higher than the mean score of the control class, which was 66.14. Based on the results of the study, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) model assisted by Thinker's Track media has a positive effect on reading comprehension skills.